The Empires' Edge : Militarization, Resistance, and Transcending Hegemony in the Pacific - Davis, Sasha, 1971- (Book collections on Project MUSE., 2015)
"In the past decade the Asia-Pacific region has become a focus of international politics and military strategies. Due to China's rising economic and military strength, North Korea's nuclear tests and missile launches, tense international disputes over small island groups in the seas around Asia, and the United States pivoting a majority of its military forces to the region, the islands of the western Pacific have increasingly become the center of global attention. While the Pacific is a current hotbed of geopolitical rivalry and intense militarization, the region is also something else: a homeland to the hundreds of millions of people that inhabit it. Based on a decade of research in the region, The Empires' Edge examines the tremendous damage the militarization of the Pacific has wrought on its people and environments. Furthermore, Davis details how contemporary social movements in this region are affecting global geopolitics by challenging the military use of Pacific islands and by developing a demilitarized view of security based on affinity, mutual aid, and international solidarity. Through an examination of 'sacrificed' islands from across the region--including Bikini Atoll, Okinawa, Hawai'i, and Guam--The Empires' Edge makes the case that the great political contest of the twenty-first century is not about which country gets hegemony in a global system but rather about the choice between perpetuating a system of international relations based on domination or pursuing a more egalitarian and cooperative future"--